Tree stand floristic dynamics in secondary forests of different ages in Sarawak, Malaysia - KARYATI KARYATI; ISA B. IPOR; ISMAIL JUSOH; MOHD. EFFENDI WASLI (Society for Indonesian Biodiversity, 2018)
Karyati, Ipor IB, Jusoh I, Wasli ME. 2018. Tree stand floristic dynamics in secondary forests of different ages in Sarawak, Malaysia. Biodiversitas 19: 767-773. Succession is a series sequential processes of the development of floristic community which involves changes in community structure, species composition and diversity over time. The information on tree stand floristic dynamics of various stages of succession in secondary forests in Malaysia is currently lacking. This study was conducted to determine tree stand structure, floristic composition, and species diversity in various stages of secondary forest development in the study areas. A total of 997, 1,842, and 834 tree stems with diameter at breast height (DBH) of > 5 cm were recorded in one-hectare-plots of 5, 10, and 20 year old secondary forests, respectively. The ten most common species in 5 and 10 year old of secondary forests consisted mostly of light demanding species. In the 20 year old secondary forest, these species did not exist. Macaranga gigantea was the most dominant tree species in the 5 and 10 year old secondary forests in terms of basal area and volume per hectare. The most common species, based on density, basal area, volume, and Importance Value Index (IVi), in the 20 year old secondary forest was Adinandra dumosa. The diversity and richness indices of the 10 year old secondary forest were the highest among all study sites.